Derivational or Inflectional Morpheme: A Case of Papuan EFL Students’ Comprehension in Narrative Text - Inna Mahjanisuri Woretma; Shilviya Irna Dwiyanti; Hasanudin; Yuliana; Ahmad Wael (UM Purwokerto Press, 2024)
The objective of this research is to scrutinize how students in the English Language Department distinguish derivational morphemes and inflectional morphemes using narrative text. Consequently, student’s obstacles in distinguishing between both of bound morphemes. Qualitative methods are employed to this research with a descriptive approach to collect and analyze derivational and inflectional morphemes. The findings revealed a total of fifty-three derivational and inflectional morphemes, comprising fifteen derivational morphemes and thirty-eight inflectional morphemes. In terms of comprehension, EFL students score 66.5 in derivational morphemes, falling under the C category, indicating a good level of understanding. For inflectional morphemes, students achieve a score of 89, placing them in the A category, signifying a very good understanding. Regarding the obstacles, students face in comprehending derivational morphemes and inflectional morphemes the main challenges are the lack of vocabulary and the lack of grammar, which make it difficult for EFL students to know word class changes and grammar function changes.